Association of serum homocysteine levels with acute kidney injury in patients with idiopathic membranous nephropathy - XIE Yi-yi; LI Qiu-lin; PAN Ling; LIAO Yun-hua (Linchuang shenzangbing zazhi)
Objective To investigate the association of serum homocysteine levels with acute kidney injury(AKI)in patients with idiopathic membranous nephropathy(IMN).Methods We retrospectively analyzed 120 participants diagnosed as IMN between March 2011 and October 2015 in the Department of Nephrology,the First Affiliated Hospital of Guangxi Medical University.The patients were divided into high Hcy group(Hcy≥10μmol/L)and normal control group(Hcy<10μmol/L)according to serum Hcy levels.The clinical baseline data of the two groups were collected,such as gender,age,blood pressure,height,weight,blood pressure,renal function,blood lipids,complements C3 and C4,CRP,serum ferritin,serum albumin and 24-h urinary protein.The differences in the clinical baseline data and the incidence of AKI between two groups were analyzed.The related factors of Hcy were analyzed.The clinico-pathological factors of AKI in patients with IMN were analyzed by Logistic regression.Results The proportion of high Hcy in IMN patients was 65.5%,and the proportion of AKI in IMN patients was 26.7%.Moreover,the incidence of AKI in the high Hcy group was significantly higher than in the normal control group(32.9% vs.14.6%,P = 0.046).The Hcy level was positively correlated with SCr level,but negatively with eGFR.Binary logistic regression analysis showed that high Hcy(OR:3.455,95% CI:1.052-11.342,P=0.041)and high blood pressure(OR:4.279,95% CI:1.586-11.544,P=0.004)were independent risk factors for AKI.Conclusions High Hcy may increase the risk of AKI in patients with IMN and controlling the level of Hcy may play an important role in the prevention and treatment of AKI in IMN patients.